Interictal epileptiform discharges affect memory in an Alzheimer's disease mouse model - Soula, Marisol; Maslarova, Anna; Harvey, Ryan E.; Valero, Manuel; Brandner, Sebastian; Hamer, Hajo; Fernández-Ruiz, Antonio; Buzsáki, György (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Interictal epileptiform discharges (IEDs) are transient abnormal electrophysiological events commonly observed in epilepsy patients but are also present in other neurological diseases, such as Alzheimer's disease (AD). Understanding the role IEDs have on the hippocampal circuit is important for our understanding of the cognitive deficits seen in epilepsy and AD. We characterize and compare the IEDs of human epilepsy patients from microwire hippocampal recording with those of AD transgenic mice with implanted multilayer hippocampal silicon probes. Both the local field potential features and firing patterns of pyramidal cells and interneurons were similar in the mouse and human. We found that as IEDs emerged from the CA3-1 circuits, they recruited pyramidal cells and silenced interneurons, followed by post-IED suppression. IEDs suppressed the incidence and altered the properties of physiological sharp-wave ripples, altered their physiological properties, and interfered with the replay of place field sequences in a maze. In addition, IEDs in AD mice inversely correlated with daily memory performance. Together, our work implies that IEDs may present a common and epilepsy-independent phenomenon in neurodegenerative diseases that perturbs hippocampal-cortical communication and interferes with memory.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Alzheimer model; interictal epileptiform discharges; memory; replay; sharp wave ripples